2008
DOI: 10.1002/app.28625
|View full text |Cite
|
Sign up to set email alerts
|

Sodium alginate and its blends with starch: Thermal and morphological properties

Abstract: A series of sodium alginate (SA) and starch blends, namely 100/0, 90/10, 80/20, 70/30, and 60/40, were processed into films by solution casting process and the obtained SA/starch blends have been characterized by differential scanning calorimetry (DSC), thermogravimetric analysis (TGA), fourier transform infrared (FTIR) spectroscopy, and scanning electron microscopy (SEM). DSC analysis shows single glass transition temperature (T g ) up to 30 wt % starch content in the blend, indicating the compatibility and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(46 citation statements)
references
References 31 publications
4
41
0
1
Order By: Relevance
“…Several authors have reported similar results for thermal degradation of alginate, e.g., Sarmento et al . (247.8 °C) and Siddaramaiah et al . (235 °C).…”
Section: Resultssupporting
confidence: 91%
“…Several authors have reported similar results for thermal degradation of alginate, e.g., Sarmento et al . (247.8 °C) and Siddaramaiah et al . (235 °C).…”
Section: Resultssupporting
confidence: 91%
“…TGA results were used to determine the degradation profiles and the residual mass of the coatings. Several steps in the weight loss curves could be observed, which are attributed to the dehydration and burning out of alginate [48]. The same degradation trend of samples DC-3 and AC-3 throughout the temperature range suggests the same composition of coatings (relative amounts of alginate and BG), thus, it could be concluded that an alternating electric field during EPD does not affect the coating composition.…”
Section: Stability Of the Colloidal Suspensionmentioning
confidence: 70%
“…The first maximum degradation temperature of different TPCS composites was found from 201 to 212°C, arisen from the decomposition temperature of glycerol . The second step found from 260 to 308°C was due to the decomposition temperatures of cassava starch and also of the sodium alginate . The two components showed the same in second‐step thermal transitions due to the similar chemical structures of starch and sodium alginate, which represented the compatible blends from the combination of two components.…”
Section: Resultsmentioning
confidence: 99%
“…It was shown that Young's modulus of the TPCS/LDPE blends modified by carrageenan increased significantly and percentage crystallinity of all the blends appeared to be similar . Sodium alginate/potato starch casted films were reported to be compatible but thermal stability of the films was found to be reduced with the increase of the starch content . Furthermore, a decrease in the elastic properties and an increase in impact resistance of the extruded thermoplastic corn starch were found when low amount (1–10 wt%) of alginate was incorporated .…”
Section: Introductionmentioning
confidence: 99%